2021
DOI: 10.3390/ijms22105163
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Pyruvate Dehydrogenase E1 as a Potential Target against Magnaporthe oryzae through Experimental and Theoretical Investigation

Abstract: Magnaporthe oryzae (M. oryzae) is a typical cause of rice blast in agricultural production. Isobavachalcone (IBC), an active ingredient of Psoralea corylifolia L. extract, is an effective fungicide against rice blast. To determine the mechanism of IBC against M. oryzae, the effect of IBC on the metabolic pathway of M. oryzae was explored by transcriptome profiling. In M. oryzae, the expression of pyruvate dehydrogenase E1 (PDHE1), part of the tricarboxylic acid (TCA cycle), was significantly decreased in respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…16 Moreover, the fungistatic and fungicidal effects of chalcones have also been investigated against phytopathogens in greater detail, including geranyl chalcones, 17 chalcone-based strobilurins, 18 dihydrochalcones (mainly phloridzin, sieboldin, trilobatin, and phloretin), 19 vanillin-chalcones, 20 ferrocenyl-chalcones, 21 isobavachalcones, 22 dihydrochromane-chalcones, 23 and isobavachalcones. 24 In contrast, the herbicidal activity of chalcones has been less investigated. Only some chalcone derivatives as inhibitors of phosphoenolpyruvate carboxylase, photosystem II, or plant growth and the herbicidal activity of flavokawains have been identified; 25−27 thus, the richly natural chalcones as herbicides are waiting to be further developed and utilized for crop protection.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Moreover, the fungistatic and fungicidal effects of chalcones have also been investigated against phytopathogens in greater detail, including geranyl chalcones, 17 chalcone-based strobilurins, 18 dihydrochalcones (mainly phloridzin, sieboldin, trilobatin, and phloretin), 19 vanillin-chalcones, 20 ferrocenyl-chalcones, 21 isobavachalcones, 22 dihydrochromane-chalcones, 23 and isobavachalcones. 24 In contrast, the herbicidal activity of chalcones has been less investigated. Only some chalcone derivatives as inhibitors of phosphoenolpyruvate carboxylase, photosystem II, or plant growth and the herbicidal activity of flavokawains have been identified; 25−27 thus, the richly natural chalcones as herbicides are waiting to be further developed and utilized for crop protection.…”
Section: ■ Introductionmentioning
confidence: 99%
“…These compounds or chalcone-rich plant extracts have competed for substantial research attention as drugs or food preservatives for decades. , Chalcones exhibit numerous interesting biological activities such as anti-cancer, anti-inflammatory, anti-hypertensive, anti-oxidant, anti-viral, anti-bacterial, and anti-microbial activities, which were several times reviewed. Recently, it has been reported that chalcones have been served as novel insecticides to control insect population, such as angular benzofuran chalcones, chemically modified chalcones, the chalcone derivatives kanakugiol, hydroxychalcone and cardamonin, and furan-chalcones . Moreover, the fungistatic and fungicidal effects of chalcones have also been investigated against phytopathogens in greater detail, including geranyl chalcones, chalcone-based strobilurins, dihydrochalcones (mainly phloridzin, sieboldin, trilobatin, and phloretin), vanillin-chalcones, ferrocenyl-chalcones, isobavachalcones, dihydrochromane-chalcones, and isobavachalcones . In contrast, the herbicidal activity of chalcones has been less investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In this research, Desmond (Desmond, Schrödinger, LLC, NY) has been used for molecular dynamic simulation (MDS) that was operated to investigate the receptor RMSD, receptor RMSF, Intra H-bonds, Cα, SASA, MolSA, Rg, and PSA for 20 ns. The RMSD values are considered to measure the average shift in a set of atoms for a specific frame with a reference frame [ 51 ]. This parameter governs a significant role in assisting the comparisons among different molecular structures and narrows down the extensive list of predictive conformations to a smaller set [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…IBC also has certain antibacterial activity against Mycobacterium tuberculosis (Chiang et al, 2010; Pollo et al, 2020). IBC can bind to PDHE1 of magnaporthe grisea to inhibit carbohydrate metabolism and eventually lead to the gradual destruction and death of mycelium cells (Li et al, 2021). In addition, IBC has certain anti‐trichomonas activity (Omisore et al, 2005).…”
Section: Pharmacological Effects Of Ibcmentioning
confidence: 99%